2011
DOI: 10.1080/08870446.2010.488265
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality predicts poor medication adherence in myocardial infarction patients

Abstract: Type D personality, the combination of negative affectivity (NA) and social inhibition (SI), is an emerging risk factor in cardiovascular disease. This study aimed to examine one possible behavioural mechanism to explain the link between Type D and ill-health. It was hypothesised that Type D personality would predict medication adherence in myocardial infarction (MI) patients. In a prospective study, 192 MI patients (54 females and 138 males) completed measures of Type D personality and provided demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 25 publications
5
79
1
5
Order By: Relevance
“…However, to-date the small number of studies that have analysed Type D as a continuous variable, and controlled for its constituent elements [11,15,16], have found no effect of Type D outcome (with the exception of one study that found that negative affectivity × social inhibition predicted medication adherence after controlling for the main effects of negative affectivity and social inhibition [29]). …”
Section: Discussionmentioning
confidence: 99%
“…However, to-date the small number of studies that have analysed Type D as a continuous variable, and controlled for its constituent elements [11,15,16], have found no effect of Type D outcome (with the exception of one study that found that negative affectivity × social inhibition predicted medication adherence after controlling for the main effects of negative affectivity and social inhibition [29]). …”
Section: Discussionmentioning
confidence: 99%
“…believing that a treatment will be less effective could lead to medication non-adherence [13]). These findings on illness perceptions fit with previous research that has identified a relationship between Type D and unhealthy behaviour [10], and medication non-adherence [13] illness perceptions were measured using the Brief IPQ and it remains to be determined if similar findings would result using the full IPQ-R. Third, the participants represented a non-consecutive sample; however, we do not believe that this had an impact in terms of selection bias, as the same inclusion criteria were applied to all potential participants. Finally, it may also be considered a limitation that we have not assessed the potential moderating effects of depression and anxiety on the relationship between Type D and illness perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural mechanisms which may explain the negative effect of Type D on clinical outcome include engaging in an unhealthy lifestyle [10], sub-optimal consultation behaviour with medical staff [11,12], and poor adherence to medication [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has observed that Type D personality is associated with adverse health outcomes in coronary heart disease, characterised by recurrent coronary events. For example, Type D status has been associated with mortality (Denollet et al, 1996), recurrent myocardial infarction (Denollet et al, 2000), treatment non-adherence (Williams et al, 2011) and depression (Denollet & Brutsaert, 1998) in coronary patients.…”
Section: Introductionmentioning
confidence: 99%